Red v izrazju - red v glavah --- in nasprotno - Kristan, Silvo (Šport (Ljubljana), 2010)
The introduction of foreign words into the Slovenian language seems to be unlimited. This phenomenon is particularly annoying in sport. Even if appropriate Slovenian terms are available, some people keep spreading foreign words for reasons that are known and unknown. It appears as if this has become a question of psychoanalysis. Sometimes there is a desire to establish a domestic term but, regrettably, examples of this reveal deficient knowledge of the notional logic which underpins the creation of technical terms. Logical flaws and nonsense are even seen in the names of the chairs at the Faculty of Sport. At the same time, the Faculty banishes philosophy (includinglogic) from the study programmes even though this field of study, besides lexicology, is fundamental not only for discussing terminological issues but also for promoting critical thought.
Keywords: šport; terminologija; tujke